2022
DOI: 10.1101/2022.01.04.474991
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Wake-Up Call: Determination of Antibiotics Residue Level in Raw Meat in Abattoir and Selected Slaughterhouses in Five Local Government in Kano State, Nigeria

Abstract: The frequent use of antibiotics may result in drug residues that can be discovered at varying quantities in animal products such as milk or meat. The presence of pharmaceutical residues in food above the MRLs has been perceived globally by various persons. Antibiotics residues are present in food, which can endanger human health by causing antibiotic sensitivity, allergic reactions, microflora imbalance, bacterial resistance to antibiotics in microorganisms, and financial loss to the food industry. Farmers aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 35 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…The world we lived in today is highly mobile, interdependent, and interconnected, giving tremendous opportunities for diseases to spread rapidly [12,13,14,15,20]. Besides, the public has been focusing on new health events caused by microbiological, toxic metals concentration and sudden environmental changes in the recent past [21,22,23,24,25,26,27,28,29]. Thus, this study revealed that the bacteria load was highest in salad and lowest microbial load in fried fish.…”
Section: Discussionmentioning
confidence: 99%
“…The world we lived in today is highly mobile, interdependent, and interconnected, giving tremendous opportunities for diseases to spread rapidly [12,13,14,15,20]. Besides, the public has been focusing on new health events caused by microbiological, toxic metals concentration and sudden environmental changes in the recent past [21,22,23,24,25,26,27,28,29]. Thus, this study revealed that the bacteria load was highest in salad and lowest microbial load in fried fish.…”
Section: Discussionmentioning
confidence: 99%
“…They are extremely carcinogenic and can result in skin, bladder, liver, and lung cancer. Arsenic exposure in humans occurs through the air, food, and water [7,[107][108][109][110]. One of the main contributors to arsenic toxicity in more than 30 nations throughout the world is drinking water [111].…”
Section: Sulphate (So 4 2-mentioning
confidence: 99%
“…Food has an important role in society through affecting people’s lifestyles, health, and habits, as well as being an important aspect of socializing [1, 2, 3, 4, 5, 6]. Today, hotels must pay greater attention to food safety, environmental protection, justice, human rights, and everything else connected to the ethical content of economic operations in the producing world [2, 7, 8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Food poisoning, unlike certain other health disorders, affects every nation, regardless of income or development level [10, 11, 12, 13, 14, 15, 16, 17, 18, 19]. Several studies have found that food-borne diseases impose a remarkable economic as well as quality-of-life burden on society through acute morbidity and chronic sequelae [2, 5, 6, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31]. Food-borne infections cover a wide range of ailments and are an increasing public and environmental health concern across the world.…”
Section: Introductionmentioning
confidence: 99%